Institutionalizing and managing corporate reputation through communication leadership among leading communication and media government– linked companies - Md Tahir, Zainal Arifin (2020)
This study was conducted in exploring and examining the aspect of corporate reputation through communication leadership of the communication and media of Government-linked companies. It angled from the government control and the presence of new technological system, involving CEOs and senior management teams. Previously, most of the studies pertaining to Government linked companies were focused on, for instance, correlation between CSR practices among higher institutions, particularly regarding corporate reputation, leadership style, and job satisfaction. Other studies were on exploring publicly listed corporations (PLCs) and Government Linked companies (GLCs) based on David's dual process model. However, there is scant research exploring the communication leadership and how it could enhances credibility towards improving corporate reputation. Data collection of this qualitative research have been made through face to face interviews involved 11 informants: five (5) CEOs and six (6) of senior management staffs of the communication and media of Government-linked companies based in Klang Valley. The informants aged between mid-twenties to late fifties, under the corporate communication division which commonly have to directly reporting to CEO office. The voice-recorded interviews replayed, transcribed, organized and undergone thematic analysis for pattern detection and theme generation where the Atlas.ti was employed. The institutional theory used to interpret the findings and guide the analysis. This theory is pertinent in view of the structural preconditions that govern and give the companies their legitimacy. A precedent study has used neo-institutional theories in explaining the interactions involved between the media, society and organisations in relation to CEO communication and positioning. This study aspires to make a specifically significant contribution to the study of communication leadership. The informants could determine on how their role as a Communication leader towards improving corporate reputation. They also give indication that, as a GLC entity, they are shouldering Government mandates. They realized that media which regards as an intangible asset, play a great role in shaping the reputation of the leader. The informants associated that as communication leader, they should demonstrate communication leadership toward improving credibility. The informants also mentioned that they need to be well acceptable as a leader by/of stakeholders. All informants also realized that the credibility of the leader and the media itself, play a great role in significantly shaping their integrity through the communication and the reputation of the organization. The informants could identify on how communication leader internalize the value of communication leadership towards improving corporate reputation. The informants see that they need to have well accepted in term of their character as a leader. They also realized that the structure/hierarchy of communication play a great role too. Additionally, the analyzed theme indicated that the internalize role also contributed to the value of communication leadership towards improving corporate reputation. In conclusion, all of three research questions have been effectively addressed and the findings from the study stand evidence to the same. The CEO and senior management team also need to apply overall principles concerning the communication leadership towards enhances credibility as well as improves corporate reputation of the communication and media of Government-linked companies.